HIV/Aids fear appeal advertisements directed at different market segments: Some considerations for corporate sponsors and NPO's - M. Terblanche-Smit; N. S. Terblanche (South African Journal of Business Management, 2013)
The purpose of social advertising is to influence human behaviour for societal benefit. Given concern about the Aids pandemic in South Africa, this study used structural equation modelling and partial least squares to investigate whetherthe use of fear in social advertising increases the likelihood of adopting appropriate behaviour pertaining to HIV/Aids prevention. Fear, attitude towards the advertisements, severity, susceptibility, response efficacy and self-efficacy were examined for their effect on behavioural intent of young adults within specific market segments. Relationships were found among susceptibility, fear, attitude, and behavioural intent, and different relationship paths were identified for segments based on gender and culture/racial groupings. These differences show the value in tailoring fear appeals to different segments when addressing social cause advertisements.
Keywords: 650